Fabrication of self-sensing soft robots via multi-material digital light processing 3D printing of hydrogels - Yifei Miao; Xiaokang Liu; Shenglin Yang; Jinghong Ma (Materials & Design, 2025)
Soft robots, known for their flexibility, can adapt to various environments and perform complex tasks. Integrating actuation and sensing into one system is essential for improving soft robots. In this study, we introduced a self-sensing soft robot fabricated by multi-material digital light processing 3D printing, which could perform real-time sensing and provide feedback on its status without external sensors. Using multi-material 3D printing, a bilayer soft robot was constructed using two specialised hydrogels: a photothermal-responsive hydrogel (rGO-P(AA-AM)-CMC) as the passive layer and a thermosensitive hydrogel (PNIPAM) as the active layer. The passive layer combined light-activated heating and strain-sensing capabilities, while the active layer enabled motion in response to temperature changes. The results showed the passive layer had high strain sensitivity (GF = 7.06), stretching ability up to 500 %, and durability across 500 loading–unloading cycles at 50 % strain. The bilayer actuator responded quickly to heat (4.1°/s), could be programmed for specific deformations, and reacted rapidly to near-infrared light. As a proof-of-concept, the robot monitored its movements in real time by detecting resistance changes. This study combined actuation and sensing into one system, addressing the challenges of separate components in soft robots and laying the foundation for smarter soft robotic systems.